2016
DOI: 10.1124/jpet.116.238824
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Leukotriene B4Action Mitigates Intracerebral Hemorrhage-Associated Pathological Events in Mice

Abstract: Infiltration of neutrophils has been suggested to play an important role in the pathogenesis of intracerebral hemorrhage (ICH) for which effective therapeutic interventions remain unavailable. In the present study we focused on leukotriene B (LTB) as a potent chemotactic factor for neutrophils in order to address its contribution to the pathologic events associated with ICH. ICH with hematoma expansion into the internal capsule that resulted in severe sensorimotor dysfunction was induced by injection of collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Methods for detecting incorporation of reactive lipids downstream of ALOX5 in vivo are not currently available, suggesting that other biomarkers will need to be developed as a proxy for NAC's ability to decrease ALOX5‐derived reactive lipids. Nevertheless, previous studies have shown that zileuton can improve functional recovery following ICH in mice …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Methods for detecting incorporation of reactive lipids downstream of ALOX5 in vivo are not currently available, suggesting that other biomarkers will need to be developed as a proxy for NAC's ability to decrease ALOX5‐derived reactive lipids. Nevertheless, previous studies have shown that zileuton can improve functional recovery following ICH in mice …”
Section: Discussionmentioning
confidence: 92%
“…Fifth, forced expression of GST isoform (GSTA 4 ), known to neutralize reactive lipids in a glutathione-dependent manner, also prevented hemin-induced toxicity in vitro ( Fig 6G). 36 Stoichiometric antioxidants, such as vitamin E or cerovive (NXY-059), have been disappointing in the clinic for stroke treatment, likely because the concentrations required for these agents to be effective are relatively high compared to therapeutic agents that work catalytically. Seventh, increases in ALOX5 and ALOX5 AP message are observed in mice, rats, and humans; NAC treatment decreased hemin-induced ALOX5 gene expression and hemin-induced oxidized lipid species (Fig 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a more recent study demonstrated that both BLT 1 and BLT 2 were rapidly upregulated after intracerebral hemorrhage (ICH) but BLT 1 was upregulated to a greater extent. Moreover, when BLT 1 knockout were compared to wild-type mice, substantially reduced neutrophil infiltration was observed in the former with no significant change in hematoma volume [42]. Unfortunately, BLT 2 knockout mice were not investigated.…”
Section: While Baseline Ltb 4 Levels Do Not Appear To Relate To Initialmentioning
confidence: 99%
“…28) Indeed, we recently obtained evidence for the involvement of LTB 4 in the pathogenesis of ICH in the internal capsule, such that blockade of LTB 4 receptor attenuated neutrophil infiltration, axonal tract damage and neurological dysfunction in mice. 29) …”
Section: Neutrophils In Axonal Tractmentioning
confidence: 99%